Teknik Pengolahan Hasil Evaluasi Belajar pada Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan di Kelas IV SDN Malangnengah II - Ina Magdalena; Khusnul Hayati; Maryanah Wulan Ningsih; Dina Rosmiyanti (Jurnal Halaqah, 2020)
The study is intended to describe (1) the techniques of processing the results of the evaluation of learning in physical education and sports subjects in fourth-grade students at SDN Malangnengah II (2) Reference for assessment of Physical Education and Sports subjects in fourth-grade students in SDN Malangnengah II (3 ) Determination of scores on Physical Education Sports and Health subjects of fourth-grade students at SDN Malangnengah II (4) Determining scores on grades Physical Education Sports and Health subjects of grade IV students at SDN Malangnengah II. This study uses a qualitative descriptive design, the subject of this study is the field teacher in the Physical and Physical Education subjects. Data collection in this study uses observation and interview methods. Analysis of the data used is the Miles and Huberman analysis model. The results of this study indicate that (1) Malangnengah II Elementary School has techniques in processing the results of evaluations in Physical and Physical Education subjects (2) there is a reference in giving scores to Physical and Physical Education subjects (3) there are ways in determining scores or scores grading raw scores in Physical and Physical Education subjects (4) Determining scores in Physical and Physical Education subjects in grade IV students at SDN Malangnengah II.